Finger Tapping Outperforms the Traditional Scale in Patients With Peripheral Nerve Damage - Zhang, Lingli; Lei, Le; Zhao, Yilong; Wang, Rong; Zhu, Yulian; Yu, Zhusheng; Zhang, Xiaojing (Frontiers in Physiology, 2018)
Objective: This study aimed to investigate whether there exist the limits of finger tapping frequency in the peripheral nerve injury detection in upper limb, and the effects of rehabilitation treatment on upper limb with peripheral nerve injury through finger tapping. Methods: Here, 54 patients with peripheral nerve injury in upper limb were selected. We conducted finger tapping frequency test and Lind-mark hand function assessment score on the 54 subjects, and recorded the data 2-week before and after rehabilitation treatment. Results: Finger tapping frequency and Lind-mark hand function assessment score have a high positive correlation regardless of the side of upper limb with peripheral nerve injury before and after the rehabilitation treatment. Finger tapping frequency of the right affected hand after treatment is significantly higher than that of before treatment (male: P < 0.05; female: P < 0.01), while finger tapping frequency of the left affected hand after treatment shows no significant difference compared to before treatment. Meanwhile, finger tapping frequency of the female subjects' unaffected hand after treatment is significantly higher than before treatment (left: P < 0.01; right: P < 0.05), however, this was not observed in male subjects. Based on data analysis, there is a high-correlation between finger tapping frequency and Lind-mark score of the patients' affected hand with brachial plexus nerve injury. A trend of the patients' affected hand with radial nerve injury is similar with brachial plexus nerve injury. Conclusion: Compared with Lind-mark score, finger tapping frequency outperformed in the aspect of speed of neural impulse conduction in patients with peripheral nerve damage.